Folate receptor 1 is a stemness trait-associated diagnostic and prognostic marker for hepatocellular carcinoma - Yuto Shiode; Takahiro Kodama; Yu Sato; Ryo Takahashi; Takayuki Matsumae; Kumiko Shirai; Akira Doi; Yuki Tahata; Hayato Hikita; Tomohide Tatsumi; Moto Fukai; Akinobu Taketomi; et al. (Biomarker Research)
Abstract Background Hepatocellular carcinoma (HCC) can be classified into several subtypes based on molecular traits, aiding in prognostic stratification. The subtype with a poor prognosis is often associated with stem/progenitor features. This study focused on identifying circulating biomarkers for aggressive HCC. Methods We searched for secretory proteins whose expression was positively associated with the stem/progenitor markers KRT19, EPCAM, and PROM1 in 2 independent HCC cohorts. Serum folate receptor 1 (FOLR1) levels were measured in 238 chronic liver disease and 247 HCC patients, evaluating their diagnostic and prognostic capabilities. Results FOLR1 was identified as a secretory protein that was positively correlated with all 3 stem/progenitor markers and a poor prognosis in both the discovery and validation cohorts. Higher FOLR1 expression was detected in tumor than nontumor tissues and was associated with aggressive subtypes, and activation of p53, DNA repair, Myc, E2F, and PI3K/AKT/mTOR pathways. Serum FOLR1 levels correlated with tumoral FOLR1 expression in HCC patients and were significantly elevated compared with those in patients with chronic hepatitis or nonliver disease. Serum FOLR1 levels demonstrated diagnostic performance for HCC comparable to that of alpha-fetoprotein (AFP), and their combination increased the diagnostic accuracy. Elevated serum FOLR1 levels were associated with poor prognosis in HCC patients, regardless of treatment, especially in patients with early-stage disease. The multivariate analysis revealed that the serum FOLR1 level and the Gender, Age, AFP-L3, AFP, and Des-gamma-carboxy prothrombin (GALAD) score were independent predictors of a poor prognosis with their combination further stratifying prognosis. Conclusions FOLR1 is a stemness-associated biomarker for HCC, with serum levels serving as a diagnostic marker for HCC and a prognostic indicator for early-stage disease.